Psychiatric Diagnoses in Individuals with Non-Syndromic Oral Clefts: A Danish Population-Based Cohort Study. - Dorthe Almind Pedersen; George L Wehby; Jeffrey C Murray; Kaare Christensen (PLoS ONE)
Background The aim of this study was to investigate the risk of psychiatric diagnoses in individuals with non-syndromic oral clefts (OC) compared with individuals without OC, including ages from 1 to 76 years. Methods Linking four Danish nationwide registers, we investigated the risk of psychiatric diagnoses at Danish psychiatric hospitals during the period 1969-2012 for individuals born with non-syndromic OC in Denmark 1936-2009 compared with a cohort of 10 individuals without OC per individual with OC, matched by sex and birth year. The sample included 8,568 individuals with OC, observed for 247,821 person-years, and 85,653 individuals without OC followed for 2,501,129 person-years. Results A total of 953 (11.1%) of the individuals with OC (9.6% for cleft lip (CL), 10.8% for cleft lip and palate (CLP) and 13.1% for cleft palate (CP)) and 8,117 (9.5%) in the comparison group had at least one psychiatric diagnosis. Cox proportional hazard regression model revealed that individuals with OC had significantly higher risk of a psychiatric diagnosis (hazard ratio (HR) = 1.19, 95% CI: 1.12-1.28). When examining cleft type, no difference was found for CL (HR = 1.03, 95% CI: 0.90-1.17), but CLP was associated with a small increased risk (HR = 1.13, 95% CI: 1.01-1.26), whereas individuals with CP had the largest increased risk (HR = 1.45, 95% CI: 1.30-1.62). The largest differences were found in schizophrenia-like disorders, mental retardation and pervasive developmental disorders, but we found no increased risk of mood disorders and anxiety-related disorders. Conclusion Individuals with non-syndromic OC had significantly higher risk of psychiatric diagnoses compared with individuals without OC. However, the elevated risk was observed for individuals with CLP and CP but not for individuals with CL and the absolute risk increase was modest.